2018
DOI: 10.2174/1871520618666180124121441
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Thieno[2,3-d]pyrimidine Derivatives and Evaluation of Their Cytotoxicity and EGFR Inhibitory Activity

Abstract: 4-Substitutedaminothieno[2,3-d]pyrimidine is a promising backbone for the design and synthesis of potent cytotoxic leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Observed agreement between kinase inhibition and antiproliferative activity can be further assessed to identify the potential inhibitors of oncogenic receptors including FLT3 receptor. However, similar to our findings, previous studies reported that compounds bearing the thieno[2,3- d ]pyrimidines scaffold exhibited inhibitory activity against kinases [ 31 , 37 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Observed agreement between kinase inhibition and antiproliferative activity can be further assessed to identify the potential inhibitors of oncogenic receptors including FLT3 receptor. However, similar to our findings, previous studies reported that compounds bearing the thieno[2,3- d ]pyrimidines scaffold exhibited inhibitory activity against kinases [ 31 , 37 ].…”
Section: Resultssupporting
confidence: 92%
“…Thus, the ability to target kinase activity represents an attractive therapeutic strategy for cancer treatment [ 30 ]. However, similar thieno[2,3- d ]pyrimidine derivatives were reported remarkable selectivity toward cancer cells as compared to normal cells [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by these facts, herein, we designed and synthesized novel cyclohepta[4,5]thieno[2,3- d ]pyrimidine derivatives as dual EGFR and VEGFR-2 inhibitors (Figure 2). The structural modifications involved replacement of 4-anilinoquinazoline scaffold with is their bioisostere thieno[2,3- d ]pyrimidine core fused to large lipophilic cycloalkyl group guided by their reported potent anticancer activity 31 , 32 . In addition, we explored the substitution of the phenyl ring of 4-anilino or 4-aryloxy moieties with, halogen, hydrogen bond donor (such as amino group), hydrogen bond acceptor (nitro, methoxy groups) or hydrogen bond donor/acceptor (sulphonylamino group) to substantiate the effect of such variations on the dual EGFR and VEGFR-2 inhibitory activity as well as their anticancer activity against MCF-7 breast cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, Ethyl 2‐amino‐6‐methyl‐4,5,6,7‐tetrahydro[1]benzothiophene‐3‐carboxylate 2 was synthesized through the reaction of 4‐methylcyclohexanone 1 with 2‐cyanoacetamide adopting Gewald method (Shearouse et al, 2014). Cyclization of the latter with formamide formed tricyclic tetrahydro[1]benzothienopyrimidine derivative 3 (Adly et al, 2018). Then, the chlorination of pyrimidinone 3 with phosphorus oxychloride using a pyridine catalyst resulted in the formation of chloropyrimidine 4 (Khalil et al, 2020).…”
Section: Resultsmentioning
confidence: 99%